Factors that influence the usage of TM Net Streamyx provided by TM Net Sdn Bhd / Nur Adham Fazuan Mohd Nor - Mohd Nor, Nur Adham Fazuan (Faculty of Business Management, 2006)
This research was conducted for the purposed of "Factors That Influence the Usage of TM Net Streamyx Provided by TM Net Sdn. Bhd.". The main objective of this research is to identify the factors that influence the usage of TM Net Streamyx provided by TM Net and to determine the level of usage for TM Net Streamyx among the customers, as need as to identify the effectiveness of the promotion activities done by TM Net in promoting the TM Net Streamyx. For the purpose of study, exploratory research design that refer to the qualitative research method had been adopted. The respondents of this study were people who lived around Seremban, N.Sembilan. 80 questionnaires had been distributed to TM Net Streamyx users and non-Streamyx users. The researcher had used nonprobability sampling method which is convenience sampling as the sampling technique. The data that had been collected was analyzed by using Statistical Package for the Social Science (SPSS) programme Version 12.0. Through the research, it shows that majority of the respondents found that packages of TM Net Streamyx is the most factors that influence the usage of TM Net Streamyx. Apart from that, most of respondents who subscribed TM Net Streamyx are male. Word of mouth communication is the most effective sources that can influence the usage of Streamyx since objective of this study have been met. Therefore, TM Net should evaluate their marketing strategy to increase its achievement in selling TM Net Sreamyx by offering good product and service, doing aggressive promotion and more price discount.